Techno-Economic Study of Biogas to Biomethane - Pages-Diaz, J (Elsevier, 2023)
Biomethane is a multipurpose and essential energy carrier in the transition toward sustainable development. Biogas to biomethane is a well-proven technology with high benefits for the environment and the economy. Yet, financial barriers still limit the deployment of its full potential. This chapter briefly introduces the main techno-economic aspects from biogas production to biomethane final use. A comprehensive discussion of capital and operational expenditures is presented based on updated data from international agencies and scientific publications. Based on the data gathered, a case study was carried out to assess the annual cost of biomethane production for gas grid injection and vehicle fuel. Finally, the role of incentives and the main challenges to overcome are presented. © 2024 Elsevier Ltd. All rights reserved.